Cross-adaptation: Heat and cold adaptation to improve physiological and cellular responses to hypoxia - Gibson, O. R.; Taylor, L.; Watt, P. W.; Maxwell, N. S. (Sports Medicine, 2017)
To prepare for extremes of heat, cold or low partial pressures of oxygen (O2), humans can undertake a period of acclimation or acclimatization to induce environment-specific adaptations, e.g. heat acclimation (HA), cold acclimation (CA), or altitude training. While these strategies are effective, they are not always feasible due to logistical impracticalities. Cross-adaptation is a term used to describe the phenomenon whereby alternative environmental interventions, e.g. HA or CA, may be a beneficial alternative to altitude interventions, providing physiological stress and inducing adaptations observable at altitude. HA can attenuate physiological strain at rest and during moderate-intensity exercise at altitude via adaptations allied to improved O2 delivery to metabolically active tissue, likely following increases in plasma volume and reductions in body temperature. CA appears to improve physiological responses to altitude by attenuating the autonomic response to altitude. While no cross-acclimation-derived exercise performance/capacity data have been measured following CA, post-HA improvements in performance underpinned by aerobic metabolism, and therefore dependent on O2 delivery at altitude, are likely. At a cellular level, heat shock protein responses to altitude are attenuated by prior HA, suggesting that an attenuation of the cellular stress response and therefore a reduced disruption to homeostasis at altitude has occurred. This process is known as cross-tolerance. The effects of CA on markers of cross-tolerance is an area requiring further investigation. Because much of the evidence relating to cross-adaptation to altitude has examined the benefits at moderate to high altitudes, future research examining responses at lower altitudes should be conducted, given that these environments are more frequently visited by athletes and workers. Mechanistic work to identify the specific physiological and cellular pathways responsible for cross-adaptation between heat and altitude, and between cold and altitude, is warranted, as is exploration of benefits across different populations and physical activity profiles.